347 Comparative effects of miR156. (7th December 2018) - Hannoufa, A; Lei, Y; Wang, Y; Yu, P
Abstract: The objectives of this study were to investigate the effects of overexpression of miR156 on nutritive values and in vitro degradations of alfalfa, in comparison with silencing SPL6 and SPL13 genes. The miR156 OE (n=5), SPL6 -silenced (SPL6 RNAi, n=3), SPL13 -silenced (SPL13 RNAi, n=3) and WT alfalfa were grown under greenhouse conditions and harvested at mid-vegetative stage for three times. Samples were freeze-dried and ground through 1mm sieve. Samples were analyzed for chemical composition, Cornell net carbohydrate and protein system (CNCPS) fractions and degradations (v6.5), and truly digestible nutrients and energetic values (NRC 2001). Duplicates samples were weighed in F57 Ankom bags and incubated at 39 °C with buffer: rumen fluid mixer (2:1 v/v) in glass bottles for 0, 2, 4, 8, 12, 24 and 48 hours. Residues were used for determiningDM and NDF degradation and kinetics. Statistical analyses were performed with Mixed procedure in SAS software. Results showed that miR156 OE had the lowest NDF and ADF contents, but the highest RDPB1, RUPB1 and energetic values. Moreover, miR156 OE had higher CB1(%CHO), but lower CB3(%CHO), RDCB3, RUCB3 and tdNDF compared to WT and SPL13 RNAi. In addition, the contents of CP, RUP and tdCP of miR156 OE were greater than WT. In contrast to SPL13 RNAi, miR156 OE had higher starch, NFC and PB1(%CP), RDCB1, RUCB1 and tdNFC than SPL13 RNAi, but lower PA2 and RUCHO. Fermentation results showed that miR156 OE had higher 48h DM degradation than SPL13 RNAi, and lower undegradable DM fraction (U) than both SPL RNAi. The 48h NDF degradations of miR156 OE was higher than WT and SPL13 RNAi. In conclusion, miR156 OE had the highest nutritive values. Overexpression of miR156 had similar, but not exactly same effects, as silencing of SPL6/13 genes, indicating that other miR156-targeted SPL genes might be also involved.